1999
DOI: 10.2165/00019053-199915020-00003
|View full text |Cite
|
Sign up to set email alerts
|

Determining Clinically Important Differences in Health Status Measures

Abstract: The objective of this article was to describe and illustrate a comprehensive approach for estimating clinically important differences (CIDs) in health-related quality-of-life (HR-QOL). A literature review and pilot study were conducted to determine whether effect size-based benchmarks are consistent with CIDs obtained from other approaches. CIDs may be estimated based primarily upon effect sizes, supplemented by more traditional anchor-based methods of benchmarking (i.e. direct, cross-sectional or longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
238
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 784 publications
(253 citation statements)
references
References 22 publications
12
238
2
1
Order By: Relevance
“…Such evidence is important for the prevention of loss of functioning among ageing employees and offers insights into potentially modifiable working conditions. Although the observed group differences in the means (table 2) and mean changes (table 3) of physical health functioning scores were fairly small, many of them were close to >3 points, which has been Mänty et al suggested as a clinically important difference (26). Our results are also in line with a previous study in this cohort which showed that adverse changes in working conditions were associated with an increased risk and favorable changes with a decreased risk of sickness absence (17).…”
Section: Discussionmentioning
confidence: 76%
“…Such evidence is important for the prevention of loss of functioning among ageing employees and offers insights into potentially modifiable working conditions. Although the observed group differences in the means (table 2) and mean changes (table 3) of physical health functioning scores were fairly small, many of them were close to >3 points, which has been Mänty et al suggested as a clinically important difference (26). Our results are also in line with a previous study in this cohort which showed that adverse changes in working conditions were associated with an increased risk and favorable changes with a decreased risk of sickness absence (17).…”
Section: Discussionmentioning
confidence: 76%
“…For the QCPR, an estimate of the points equivalent of the SMD was obtained by taking the baseline SD for the QCPR and multiplying by the effect size 53 of 0.35 set for the study. This gave a difference of 3.1.…”
Section: Valuation Strategy For Outcomesmentioning
confidence: 99%
“…At the time of planning the study, previous studies in a range of populations and conditions had suggested that a minimum clinically important difference on the SF-36v2 PCS was about 4 points [0.4 standard deviation (SD)], [74][75][76][77] although the latest version of the SF-36v2 manual now suggests that 'a minimum important difference of 2-3 points is reasonable'. 78 In this study, a difference of no greater than 2 points was conservatively specified as demonstrating equivalence.…”
Section: Sample Size and Powermentioning
confidence: 99%